Indicators System Creation For The Energy Efficiency Benchmarking Of Municipal Power System Facilities - Davydenko L.V. (Problems of the Regional Energetics, 2015)
The issues of the dataware of the comparative analysis procedure (benchmarking) for municipal power system facilities energy efficiency level estimation with a view of the hierarchical structure of the heat supply system are considered. The aim of the paper is the system of indicators formation for characterizing the efficiency of energy usage as on objects on lowest so on highest levels of power systems, proceeding from features of their functioning. Benchmarking methodology allows carrying out the estimation of energy efficiency level on the base of a plurality of parameters without their generalization in one indicator, but requires ensuring their comparability. Using the methodology of available statistical information that did not require deep specification and additional inspection structuring objectives and tasks of energy efficiency estimation problem has been proposed for ensuring the opportunity of benchmarking procedure implementation. This makes it possible to form the subset of indicators that ensure enough specification of the object of study, taking into account the degree of abstraction for every hierarchical level or sub problem. For a comparative analysis of energy using efficiency in municipal power systems at the highest levels of the hierarchy a plurality of indicators of the energy efficiency has been formed. Indicators have been determined with consideration of the structural elements of heat supply systems, but allowing taking into account the efficiency of the initial state of the objects, their functioning, and the questions of energy resources accounting organization. Usage of the proposed indicators provides implementation of energy using efficiency monitoring in the municipal power system and allows getting complete overview of the problem.